Prediction of wrinkling using finite element simulation - Mohd Fizree, Abdul Razak (2013)
Deep drawing is a process for shaping flat sheets into cup-shaped articles without fracture or excessive localized thinning. The design and control of a deep drawing process depends not only on the work piece material, but also on the condition at the tool work piece interface, the mechanics of plastic deformation and the equipment used. This final project is about prediction of wrinkling in deep drawing part. The prediction methods can be broadly divided into two categories which is by experimental and simulation. The project deals with the Finite Element Analysis (FEA) and one step simulation of cup 50 mm using Altair Hyperform. In this project, the effect of some variables like blank holder force, blank thickness and drawn depth are investigate on flange wrinkling. Based on the result, the first analysis shows that wrinkle will occurred when the blank holder force is low. By increasing the blank holder force, the wrinkle is reducing. Second analysis shows that more thicker part will decreased tearing ratio due to the strength and stiffness of material. The last analysis give a result on effect of blank holder force and drawn depth on flange wrinkling where as if the depth increased, the percentage of wrinkling also increased. FEA software can be effectively used not only to predict the extent of damage, but damage control measures can also be simulated to suggest appropriate action to be taken at forming stages.